Three kinds of regulatory signals for production of juvenile hormone in females of the linden bug, Pyrrhocoris apterus - Hodkova, Magdalena; Okuda, Takashi (Journal of insect physiology, 2019)
Three types of regulation of the corpus allatum (CA) activity were defined in females of the linden bug Pyrrhocoris apterus. First, short-term inhibition of the CA activity was found in starved or fed long-day females, or in short-day females. Inhibitory factor(s) are transmitted to the CA via nerves, but in vitro they might reach the CA via the incubation medium. Origin of the inhibition is the pars intercerebralis (PI). The inhibitory effect is reversible during short-term incubation in vitro. This short-term inhibition can be quickly restored by the presence of the brain-suboesophageal ganglion (BR-SG) with the PI or removed, by the presence of the BR-SG without the PI or by the absence of the BR-SG. Short-term inhibition is sufficient to inhibit the CA of starved long-day females, but it is not strong enough to inhibit the CA of diapausing bugs. Second, developmental stimulation of the CA activity by feeding in long-day females is associated with growth in size of the CA. Stimulation proceeds slowly (days) in vivo and reaches the CA from the PI via nerves. Activity of the CA is irreversible in vitro; it is maintained without any further stimulation by the PI, i.e. in the presence of the BR-SG without PI or in the absence of the BR-SG. In the intact BR-SG-CC-CA the developmental stimulation of the CA is compensated by short-term inhibition of similar strength. Therefore, the activity of large CA within the intact BR-SG-CC-CA (stimulated + inhibited) is similar to the activity of the small denervated CA (no stimulation + no inhibition). Third, long-term inhibition of the CA activity in short-day females, produced by the diapause inducing photoperiod in the PI, reaches the CA via nerves. However, in contrast to the short-term inhibition of the CA, it is irreversible during short-term incubation in vitro. The long-term inhibition can only be removed several days after disconnection of the CA from the brain in vivo.
Keywords: Animals; Nervous connection; Female; Starvation; Juvenile Hormones; ženské pohlaví; Corpora Allata; stravovací zvyklosti; corpora allata; Short-term inhibition; signální transdukce; mozek; Signal Transduction; Feeding; Pars intercerebralis; Long-term inhibition; Cytological stimulation; Feeding Behavior; Brain; juvenilní hormony; zvířata; Photoperiod; fotoperioda; Heteroptera